2014
DOI: 10.2355/isijinternational.54.2084
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Diffusivity Measurement of Oxide Scale Formed on Steel during Hot-rolling Process

Abstract: Thermal diffusivity and conductivity of oxide scales formed on steel plates are essential to control the cooling rate of the steel in the hot-rolling process. A flash method was applied to measure the thermal diffusivity of oxide scales. Sample specimens were commercial hot-rolled plates on which about 25 μm-thick oxide scales were formed. The results of the flash measurement with the analysis for two-layered sample provided an average thermal diffusivity value of 7.3 × 10 -7 m 2 s -1 for the oxide scale. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
(35 reference statements)
1
21
0
Order By: Relevance
“…For such mathematical simulations, the thermal conductivity and diffusivity of the iron oxide scale are the most important thermophysical properties. 4) To date, to the best of the authors' knowledge, there have been six reports on the thermal conductivity/diffusivity of iron oxide scales; [5][6][7][8][9][10] each has reported that the thermal conductivities/diffusivities of iron oxide scales are smaller than those of steel. Three of these studies have obtained the thermal diffusivities of single-phase samples of sintered iron oxides as functions of temperature.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For such mathematical simulations, the thermal conductivity and diffusivity of the iron oxide scale are the most important thermophysical properties. 4) To date, to the best of the authors' knowledge, there have been six reports on the thermal conductivity/diffusivity of iron oxide scales; [5][6][7][8][9][10] each has reported that the thermal conductivities/diffusivities of iron oxide scales are smaller than those of steel. Three of these studies have obtained the thermal diffusivities of single-phase samples of sintered iron oxides as functions of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the sintered iron oxide samples, actual iron oxide scale has a multilayered structure of Fe 2 O 3 , Fe 3 O 4 , and FeO phases, and also contains pores. 8) Even if accurate thermal conductivity/ diffusivity values are known for single-phase iron oxides, it is extremely difficult to predict the values of an actual iron oxide scale. Thus, sintered iron oxide samples are not suitable representatives of an actual iron oxide scale.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mu LI, 1) * Rie ENDO, 1) Li Ju WANG, 2) Lei LI 2) and Masahiro SUSA 1) 1) Department of Metallurgy and Ceramics Science, Tokyo Institute of Technology, Ookayama, Meguro-ku, Tokyo, 152-8552 Japan.…”
Section: A New Methods For Apparent Thermal Conductivity Determinationmentioning
confidence: 99%